The role of government in helping SMEs to access finance: An evolutionary game modeling and simulation approach. - Zhu Mei; Jingjing Zhang; QiaoMei Zhou (PLoS ONE)
Purpose This study aims to delineate the operating system of a strategic game model involving three core financial actors-government, banks, and guarantee institutions, with a focus on their collective impact on system evolution towards sustainable SME financing. Methodology Utilizing numerical simulations informed by dynamic equation constraints and optimal equilibrium states, this paper abstracts the strategic behaviors of system constituents, constructing a game model to predict and analyze system evolution within various operational contexts. Results The simulation experiments reveal the critical role of quality risk information and responsible actor behavior in maintaining low default rates and fostering a sustainable financial system. System trajectories under various scenarios highlight the fragility of the equilibrium and the necessity of concerted, strategic cooperation among all stakeholders. Conclusions Findings underscore the importance of a cooperative, conscientious approach by government, banks, and guarantee institutions to ensure a robust and sustainable SME financing environment. The study advocates for strategic policy guidance, emphasizing the interconnectedness of institutional roles and their cumulative effect on system stability.